(NmUZYKA I DETIs - (Nn(B. (NmIHAJLOWSKAQs ((NmOSKWAs (NsOWETSKIJ KOMPOZITORs, 1977)
(NkNIGA OZNAKOMITX [IROKIJ KRUG ^ITATELEJ S RAZLI^NYMI METODAMI MUZYKALXNO(B-(N\STETI^ESKOGO WOSPITANIQ(B.s
Keywords: (NiSPOLNITELXSTWOs